Human Resources in Dentistry in the Unified Health System (Research, Society and Development, 2022)
The public health workforce studies are scarce, particularly in dentistry. This longitudinal study of the dentistry human resources in the SUS primary and secondary care was based on microdata from the National Program to Improve Access and Quality of Primary Care evaluation and was intended to analyze the hiring, type of employment relationship and hiring mechanism of dental surgeons, taking the population size of the municipalities into consideration, in the Brazilian Unified Health System (SUS) primary and secondary care. The data was evaluated through descriptive statistical analysis and paired t test. It was concluded that considering the population size of the municipalities, the differences in the contract types, employment relationship and the way of hiring in the metropolises and in the small and medium size municipalities were evident. In the secondary care, the highest salaries are concentrated in large size municipalities and in the metropolises; evidencing a lack of regulation in the State and the need for policies which involve the human resources management at SUS.